The Effect of Incentives and Non-Financial Performance on Managerial Performance - Okta Malinda; Fajar Gustiawaty Dewi; Rindu Rika Gamayuni (Universitas Prasetiya Mulya, 2019)
The purpose of this study is to provide empirical evidence about the effect of incentives and non-financial performance on managerial performance at private universities in Lampung. This research was conducted at private universities in Lampung with its unit of analysis C-accredited study program which has 164 study programs, consisting of 68 study programs at the University, 1 study program at the Institute, 67 study programs at the Collages, 4 study programs at the Polytechnic and 24 study programs at the Academies. The data analysis method used is a quantitative method with the Structural Equation Model (SEM) model. The results of this study indicate that both incentives and non-financial performance allowances have a significant positive effect on managerial performance. The implication of this research is that the incentive variable provides additional indicators not only limited to bonuses and rewards but also in the form of professional allowances & honor.Keywords: Managerial Performance, incentives, Non-financial Performance(1,2,3&4) Faculty Economics and Business, Accounting Department, Lampung University, Indonesia* Corresponding Author https://doi.org/10.21632/irjbs.12.1.41-54